Bactericidal urea crown ethers target phosphatidylethanolamine membrane lipids. Issue 17 (13th April 2021) - Herschede, Sarah R.; Gneid, Hassan; Dent, Taylor; Jaeger, Ellen B.; Lawson, Louise B.; Busschaert, Nathalie
Abstract : In this manuscript we report a small molecule that can selectively bind to the bacterial lipid phosphatidylethanolamine and consequently functions as an antibacterial agent against certain Gram-positive bacteria. Abstract : An increasing number of people are infected with antibiotic-resistant bacteria each year, sometimes with fatal consequences. In this manuscript, we report a novel urea-functionalized crown ether that can bind to the bacterial lipid phosphatidylethanolamine (PE), facilitate PE flip-flop and displays antibacterial activity against the Gram-positive bacterium Bacillus cereus with a minimum inhibitory concentration comparable to that of the known PE-targeting lantibiotic duramycin.